Evaluasi Usability Aplikasi Bank Syariah Indonesia Mobile menggunakan Metode Usability Testing dan System Usability Scale (Studi Kasus : KCP Trenggalek Sudirman 1) - Annisa Julia Santoso; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Bank Syariah Indonesia Mobile (BSI Mobile) is one of the distribution channels owned by Bank Syariah Indonesia to access customer accounts using 3G/4G technology and wifi via smartphones. This application receives a lot of negative reviews related to usability on the Play Store. In this research, an evaluation was carried out to determine the usability level of the BSI Mobile application using usability testing and system usability scale (SUS) methods to produce application improvement recommendations. Respondents in this study were customers of KCP Trenggalek Sudirman 1. Usability test respondents were 5 respondents and new users. SUS respondents are 30 active users of the BSI Mobile application and android users. The measurement on the learnability aspect is 65%, the efficiency aspect is 0.008 goals/sec, and the error aspect is 0.24 (relatively small). The satisfaction aspect uses the SUS method which is filled out by 30 respondents with a result of 70.75 so that is in the acceptable category and gets a C rating (good). Interviews were conducted to dig deeper into the problems experienced by respondents during usability testing. Based on the results of usability testing and interviews, there are 6 findings of usability problems. Therefore, respondents provide suggestions and guidelines sourced from google material design to make recommendations for improvement.